Pengaruh Kegiatan Pengayaan pada Konsep Hukum Pascal Berdasarkan Pendidikan STEM pada Keterampilan Berpikir Kritis dan Kreatif pada Siswa Kelas 8 - Diah Mayasari (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2019)
The study about investigation of The Effect of Enrichment in the Concept of Pascal-laws Based on STEM education on critical and creative thinking skills of 8th-grade Students are conducted as an effort to follow up the lack of development of Critical and Creative Thinking Skills on the students. The research was conducted using quasi-experiment design, the type of the one group pretest-posttest designs and involved eighth-graders aged between 14-15 years as research subjects for five meetings. The data was obtained through student worksheets and observations. Data processing to see N-Gain was used Microsoft Excel 2007 and the results showed that there was an increase in the percentage of critical thinking skill scores from 58% (pretest) to 89% (post-test) with high category increase (N-gain = 0.74). while student creativity also rose from 15% (pretest) to 81% (post-test) with moderate category increase (N-gain = 0.68). Students' creation tools on STEM's educational enrichment program are Hydraulic Glass Cleaners.